Is xylitol a sweet revolution? - A literature review of its metabolic effects and innovative applications - Blecharczyk, Małgorzata; Zydlewski, Igor; Mrozek, Martyna; Nowik, Alicja; Pacanowska, Martyna; Sękulski, Marcin; Kosiński, Maciej; Jakubiec, Paweł (Quality in Sport, 2025)
Introduction: Xylitol is a natural sweetener clasified as a sugar alcohol. It tastes and looks like sugar, but has a 40% lower caloric value. Sugar alcohols are becoming more popular not only in overweight or diabetic patients, but also in everyday life of young, athletic people. Xylitol has been studied since the 1960s for its antihyperglycemic, antiobesogenic and antidiabetic potential [1], and its health effects have been confirmed in many studies over the years, which is why they are often used in dental care products and chewing gums [2]. This polyol seems to be very promising in supporting treatment of various diseases. It is known that its metabolic effect is different from glucose metabolism, but the effects of xylitol on the body are still not fully understood, which creates a wide range of potential applications for xylitol. Aim of the study: The purpose of this study is to evaluate the influence of xylitol on human metabolism and to review innovative ideas of its use based on randomized clinical trials and clinical trails published in the last five years. Material and Methods: Review and analysis of randomised clinical trials and clinical trials from 2020-2025 available on PubMed and Google Scholar. Conclusions: Xylitol is definitely promising as an alternative sweetener. With its sweetness and slightly impact on postprandial glycemia it can be consumed as a sugar substitute, also in combination with a high protein meal. However, xylitol may gain much wider application than just a sweetener - by supporting the symptomatic treatment of gastroesophageal reflux disease (GERD) and good osmometabolic properties during peritoneal dialysis (PD), it seems to maintain the benefits of traditional therapies while avoiding side effects. Most of the studies published so far on innovative use of xylitol were pilot studies, therefore metabolic regulation, brain network modulation and general long-term impact of xylitol on health needs extensive studies.